CONCEPTUAL ANALYSIS OF MAQÃSHID SYARI’AH ABDUL ATHÎ AND THE IMPLICATIONS IN RESPONDING TO THE SOCIAL PHENOMENON OF TA’ARRUF ONLINE - Udin Supriadi,; Wawan Hermawan; Risris Hari Nugraha; Mohammad Rindu Fajar Islamy (Universitas Islam Negeri Mataram, 2021)
The purpose of this study is to explore the conceptual Maqãshid Syari’ah developed by an Egyptian fiqh expert Muhammad Abdul Athî Muhammad Ali, and its implications in reconstructing fiqh as an effort to respond to the symptoms of new social phenomena in today’s society. Recently, there have been many community social activities labeled as Islam, but at the practical level, they are indicated to be contrary to the principles of Islamic teachings. One of these phenomena is Ta’arruf online, where Ta’arruf has become a new lifestyle for some Muslims, especially those who have just made the hijrah process. However, this phenomenon is alleged to be another method to get a partner to marry quickly, which the Ikhwan (male) uses to trick the Akhwat (women) who vent their lust or lust. The theory developed by Abdul Athî, a senior scholar at Al-Azhar University in Egypt, attempts to reconstruct the thinking paradigm of the millennial generation in viewing online ta’arruf as a symptom of a social phenomenon. The limited understanding of the millennial generation towards religion sometimes triggers and gives birth to new problems. Through a library study of his main work entitled Al-Maqãshid Al-Syar’iyyah wa Atsãruhã fî Al-Fiqh Al-Islãmî and several other works as well as data analysis by Miles and Huberman, the results show thatIn the perspective of Al-Athi’s maqãshid Sharia, producing a fiqh law today must be built with the principle of prudence, supported by an in-depth study of the condition of society, so that a clear fiqh rule is born that can solve solutions, not problems.